2000
DOI: 10.1136/bmj.320.7239.904
|View full text |Cite
|
Sign up to set email alerts
|

Private funding of elective hospital treatment in England and Wales, 1997-8: national survey

Abstract: Methods and resultsInformation on patients admitted as inpatients or day cases during sample periods in financial year 1997-8 were obtained from 215 of 221 acute independent hospitals with operating departments in England and Wales 2 ; data obtained included the patient's clinical status, demographic information, and source of funding for the procedure. Numbers for the whole year were estimated by weighting the sample data according to the duration of sampling, the time of year, and the number of hospitals tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 4 publications
0
26
0
Order By: Relevance
“…Estimates of the number of private revascularizations not included in the HES dataset varies from 7 to 30 percent (Black, Langham, and Petticrew 1995; Williams et al 2000), and 12.5 percent in London (Mindell et al 2008), so the national differences in the use of revascularization may not be as large as these data suggest. As we discuss below, however, counting privately financed revascularization may point to even greater, inequalities in access among older persons.…”
Section: Access To Specialty Carementioning
confidence: 92%
See 1 more Smart Citation
“…Estimates of the number of private revascularizations not included in the HES dataset varies from 7 to 30 percent (Black, Langham, and Petticrew 1995; Williams et al 2000), and 12.5 percent in London (Mindell et al 2008), so the national differences in the use of revascularization may not be as large as these data suggest. As we discuss below, however, counting privately financed revascularization may point to even greater, inequalities in access among older persons.…”
Section: Access To Specialty Carementioning
confidence: 92%
“…It is likely that the English rates are underestimated because of the exclusion of those surgeries that are paid for privately. This could amount to 25 percent of the total surgeries performed (Williams et al 2000). The proportion of private surgeries is likely to be highest among the youngest age groups because, unlike in the United States, in England private insurance coverage is highest among those aged fifty-five to sixty-four because it is usually an employment benefit (Eoubister et al 2006).…”
Section: Access To Specialty Carementioning
confidence: 97%
“…Appleby and Yates (1995) estimated that in 1986 about 20% of the elective surgical procedures were carried out in private beds in public hospitals. More recent data on private funding of elective hospital treatment in England and Wales in 1997±8 (Williams et al, 2000) indicated that 14.5% of the patients had had private funding. However, only one in ten private patients were treated in NHS hospitals and only 1.6% of the total number of surgical and medical procedures performed in NHS hospitals concerned privately funded patients.…”
Section: Pms In Selected Oecd Countries: Experience and Lessonsmentioning
confidence: 96%
“…However, only one in ten private patients were treated in NHS hospitals and only 1.6% of the total number of surgical and medical procedures performed in NHS hospitals concerned privately funded patients. Of the private admissions, 81% were funded by insurance and the patient funded 18% (Williams et al, 2000). In the UK, as in Israel, over two-thirds of the hospital-based operations are customarily not elective (Appleby and Yates, 1995).…”
Section: Pms In Selected Oecd Countries: Experience and Lessonsmentioning
confidence: 98%
“…Despite the steady increase in the number of publicly funded operations conducted in England during the 1970s and 1980s, the number privately funded rose in tandem, maintaining a steady 13-15% of all procedures. 5 This suggests that the average surgeon chose to spend about 14% of his or her time operating privately and this proportion did not change over two decades, despite major increases in the number of public sector operations.…”
mentioning
confidence: 99%